Surveillance and Outcomes of Pediatric Hematopoietic Stem Cell Transplantation Recipients During the Recent COVID-19 Outbreak in China - Wang X; Yu U; Ding C; Ye H; Wang C; Yang C; Li Y; Zhou X; Zhang Q; Liu S; Wen F (Infection and Drug Resistance, 2023)
Xiaodong Wang,1,2,* Uet Yu,2,* Chao Ding,2,3 Huiying Ye,2 Chunjing Wang,2 Chunlan Yang,2 Yue Li,2 Xiaohui Zhou,2 Qian Zhang,2 Sixi Liu,2 Feiqiu Wen1,2 1Department of Pediatrics, First Affiliated Hospital of Jinan University, Guangzhou, People’s Republic of China; 2Department of Hematology and Oncology, Shenzhen Children’s Hospital, Shenzhen, People’s Republic of China; 3Discipline of Pediatrics, China Medical University, Shenyang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Feiqiu Wen, Department of Pediatrics, First Affiliated Hospital of Jinan University, Guangzhou, People’s Republic of China, Email fwen62@163.com Sixi Liu, Department of Hematology and Oncology, Shenzhen Children’s Hospital, 7019 Yitian Road, Futian, Shenzhen, 518038, People’s Republic of China, Email tiger647@126.comBackground: The COVID-19 pandemic presents challenges for healthcare systems globally, especially in vulnerable populations such as pediatric hematopoietic stem cell transplant (HSCT) recipients. This study examines the clinical characteristics and outcomes of COVID-19 infection in pediatric HSCT recipients within one year post-HSCT.Methods: Retrospective analysis was conducted on data from 247 pediatric patients. None of them had received SARS-CoV-2 vaccination or had prior infection. SARS-CoV-2 infection was confirmed using RT-PCR testing. COVID-19 disease severity was categorized according to established guidelines. Demographic, clinical, laboratory, imaging and treatment data were collected.Results: The median age of the cohort was 7± 3.7 years, with thalassemia major as the predominant underlying disease. Allogeneic HSCT was performed in the majority of cases, with haploidentical donors being the most common source of grafts. Nearly half of the patients developed COVID-19, with significantly higher infection rates observed in recipients over 100 days compared to recipients within 100 days post-HSCT (40.1% vs 21.7%, p< 0.05, Fisher’s Exact test). Fever (n=107, 43.2%) and cough (n=88, 35.6%) were the most common symptoms. While most patients had mild disease and did not require specific anti-viral treatment, a significant proportion required hospitalization (n=34, 13.8%). Various treatments were employed hospitalized patients, including Paxlovid (n=19, 55.9%), methylprednisolone (n=7, 20.6%), IL-6 antibody (n=2, 5.9%), mesenchymal stem cells (n=3, 8.8%), and exosomes nebulization therapy (n=2, 5.9%). Despite multidisciplinary approaches, one patient died from severe respiratory failure. However, overall survival of all patients remained high (99.53%; CI 96.72– 99.93%), indicating favorable outcomes in pediatric HSCT recipients with COVID-19.Conclusion: This study provides insights into clinical features, therapeutic measures, and outcomes of pediatric HSCT recipients following COVID-19 infection in a large HSCT center in China. These findings contribute to our understanding of COVID-19 in this population and inform strategies to mitigate the impact the pandemic’s impact on their care.Keywords: COVID-19, SARS-CoV2, hematopoietic stem cell transplantation, pediatrics